Conformity of Vertical Public Housing's Performance With Resilience Agenda in Bandung Metropolitan Area - Allis Nurdini; Nur Fitra Hadianto (Indonesian Journal of Science and Technology, 2018)
The ideas of resilient housing have been rapidly developed for better future quality improvement. On the other side, resilience is a critical framework, which is not only for housing in the future but also for those that have been built and already inhabited. Therefore, it is necessary to conduct a study that can identify the compatibility of existing housing performance with the framework of resilience. Five vertical housing in Bandung were selected as case studies. These five housing are vertical public-housing prototype from national government that have been used in many cities for low income people. Post occupancy evaluation was used to assess the performance. Benchmarking and occupant survey instruments were combined in this study. The performance measurement results were then compared with critical resilient framework for housing to support community livelihood, reduce the vulnerability of resident to environmental risk and stresses, enhance personal security, and empower communities. It is concluded that the resilience of existing vertical public housing is differentiated according to the corridor design type and the occupant behavior to adapt the design. These two factors are closely linked to the achievement of resilient housing framework and are key inputs for short-term improvements in the vertical public housing that have been built.